2021
DOI: 10.1186/s12882-021-02289-y
|View full text |Cite
|
Sign up to set email alerts
|

Home-based exercise and bone mineral density in peritoneal dialysis patients: a randomized pilot study

Abstract: Background The prevalence of osteopenia and osteoporosis is higher in patients with chronic kidney disease than that in the general population. Although physical exercise prevents bone loss in hemodialysis (HD) patients, previous studies have not focused on peritoneal dialysis (PD) patients. Therefore, we aimed to evaluate the effects of home-based exercise on bone mineral density (BMD) in patients with PD. Methods Stable outpatients undergoing PD … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 37 publications
2
9
0
1
Order By: Relevance
“…On the other hand, the present's results are in line with the results obtained by Tayebi et al (2018) who showed that exercise during hemodialysis had no significant effect on serum levels of Albumin in intervention group [11]. The results of the present study are not in line with the results the study by Watanabe et al (2021), that showed homebased exercise could not significantly affect serum levels of Albumin, Calcium and phosphate [16]. The reason for this difference is maybe the use of different intervention methods and the difference in the duration of the exercise (6 months compared to 8 weeks).…”
Section: Discussionsupporting
confidence: 83%
“…On the other hand, the present's results are in line with the results obtained by Tayebi et al (2018) who showed that exercise during hemodialysis had no significant effect on serum levels of Albumin in intervention group [11]. The results of the present study are not in line with the results the study by Watanabe et al (2021), that showed homebased exercise could not significantly affect serum levels of Albumin, Calcium and phosphate [16]. The reason for this difference is maybe the use of different intervention methods and the difference in the duration of the exercise (6 months compared to 8 weeks).…”
Section: Discussionsupporting
confidence: 83%
“…Furthermore, the results of our study are in line with the findings obtained by Kopple et al, who observed that exercise during hemodialysis had no significant effect on serum levels of albumin in the patients of the intervention group (11). The findings of the present research are not in line with the findings of Watanabe et al, where home-based exercise could not significantly affect serum levels of albumin, calcium and phosphate (16). This difference may be related to the use of different exercise programs and the difference in the duration of the exercise (six months compared to eight weeks).…”
Section: Discussionsupporting
confidence: 82%
“…28 Koufaki et al 29 Manfredini et al 12 Molsted at al. 20 Luo et al 32 Rouchon et al 19 Shahgholian et al 25 Sheshadri et al 31 Uchiyama et al 26 Watanabe et al 27 Lo et al 22 Straub et al 13 Musculoskeletal adverse events were the most frequent accounting for 14 (47%) of 32 reported intervention-related adverse events. This finding is not unexpected as these events account for the majority of adverse events resulting from exercise and physical activity in both healthy and chronic disease populations.…”
Section: Discussionmentioning
confidence: 99%
“…From the 11, 2 studies 19,20 (8%) provided data upon request, 1 study 13 (4%) did not respond to a request for data however reported withdrawal data were accepted in lieu of adverse event data and 8 studies did not respond to requests for adverse event data (and did not have reported withdrawal data that could be used in lieu). Eight studies [21][22][23][24][25][26][27][28] (32%) reported full adverse event data in-text; four studies 12,[29][30][31] (16%) provided partial adverse event data in-text, with authors providing further data and/or clarification on request, two studies 32,33 (8%) reported partial adverse event data in-text, but did not provide additional details on request to enable proper classification. This resulted in 17 studies being included in the final review.…”
Section: Study Selectionmentioning
confidence: 99%
See 1 more Smart Citation